2013
DOI: 10.1186/1471-2393-13-s1-s7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of primary human myometrial cell culture models to study pregnancy and labour

Abstract: Background The development of the in vitro cell culture model has greatly facilitated the ability to study gene expression and regulation within human tissues. Within the human uterus, the upper (fundal) segment and the lower segment may provide distinct functions throughout pregnancy and during labour. We have established primary cultured human myometrial cells, isolated from both upper and lower segment regions of the pregnant human uterus, and validated them for the purpose of studying human pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 34 publications
3
38
1
1
Order By: Relevance
“…Furthermore, the comparison between primary and telomerase-immortalized cells revealed no significant differences in signaling pathways, such as epidermal growth factor (EGF)-stimulated phosphorylation of the EGF receptor, insulinstimulated Akt phosphorylation, oxytocin and lysophosphatidic acid-stimulated extracellular signal-regulated kinase (ERK) 1 and 2 phosphorylation, myosin light chain (MYL) phosphorylation, and interleukin-1 induction of IκBα degradation [25]. Although this study found no significant difference between immortalized and primary cell lines, it has been suggested that immortalization could cause fundamental changes in the cells [26], and as such many studies use primary cells only at low passages (passage five and lower) [27].…”
Section: Human Myometrial Smooth Muscle Cell Culture Modelscontrasting
confidence: 60%
See 4 more Smart Citations
“…Furthermore, the comparison between primary and telomerase-immortalized cells revealed no significant differences in signaling pathways, such as epidermal growth factor (EGF)-stimulated phosphorylation of the EGF receptor, insulinstimulated Akt phosphorylation, oxytocin and lysophosphatidic acid-stimulated extracellular signal-regulated kinase (ERK) 1 and 2 phosphorylation, myosin light chain (MYL) phosphorylation, and interleukin-1 induction of IκBα degradation [25]. Although this study found no significant difference between immortalized and primary cell lines, it has been suggested that immortalization could cause fundamental changes in the cells [26], and as such many studies use primary cells only at low passages (passage five and lower) [27].…”
Section: Human Myometrial Smooth Muscle Cell Culture Modelscontrasting
confidence: 60%
“…Mosher et al [26] established primary cultures of human myometrial cells isolated from paired upper and lower segment uterine biopsies for 10 passages and determined the expression of smooth muscle markers, fibroblast markers, contractile proteins or labor-associated proteins over time. It was found that both upper and lower segment human myometrial cells stably expressed smooth muscle markers (α-SMA, calponin, caldesmon, tropomyosin) and fibroblast markers (vimentin, 1B10) to at least 10 passages [26].…”
Section: Human Myometrial Smooth Muscle Cell Culture Modelsmentioning
confidence: 99%
See 3 more Smart Citations